2005
DOI: 10.1124/dmd.105.007435
|View full text |Cite
|
Sign up to set email alerts
|

EXPRESSION OF UDP-GLUCURONOSYLTRANSFERASE ISOFORM mRNAS DURING INFLAMMATION AND INFECTION IN MOUSE LIVER AND KIDNEY

Abstract: ABSTRACT:Inflammation or infection down-regulates the activity and expression of cytochrome P450 (P450) enzymes involved in hepatic drug clearance, possibly altering drug effectiveness and leading to toxicity. The regulation of UDP-glucuronosyltransferases (UGTs) in inflammation and infection is less well characterized. To determine the response of hepatic and renal UGTs during inflammation and infection, mice were administered either saline or 1 mg/kg lipopolysaccharide (LPS) (16 h), or Citrobacter rodentium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 16 publications
3
42
0
Order By: Relevance
“…The references in the current literature concerning the transcriptional regulation of UGTs in liver injury are largely controversial. Some reports showed that most UGT isoforms were transcriptionally downregulated in the liver samples from humans with liver diseases, which was found to correlate with inflammation but not with fibrosis scores (Congiu et al, 2002), and from the liver samples of mice treated with lipopolysaccharides or bacterial infections (Richardson et al, 2006). However, another set of reports witnessed an up-regulation of most UGT isoforms in humans with cirrhosis (Debinski et al, 1995) and rat liver samples (Debinski et al, 1996), as well as in regenerated rat liver tissues after partial hepatectomy (Pellizzer et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The references in the current literature concerning the transcriptional regulation of UGTs in liver injury are largely controversial. Some reports showed that most UGT isoforms were transcriptionally downregulated in the liver samples from humans with liver diseases, which was found to correlate with inflammation but not with fibrosis scores (Congiu et al, 2002), and from the liver samples of mice treated with lipopolysaccharides or bacterial infections (Richardson et al, 2006). However, another set of reports witnessed an up-regulation of most UGT isoforms in humans with cirrhosis (Debinski et al, 1995) and rat liver samples (Debinski et al, 1996), as well as in regenerated rat liver tissues after partial hepatectomy (Pellizzer et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…UGT activities were found largely preserved in liver diseases, possibly because of the activation of latent UGT enzymes (Desmond et al, 1994), the increased expression in remaining viable cells (Debinski et al, 1995), and the increased contribution of extrahepatic UGTs (Omar et al, 1996). However, more recent studies focusing on the mRNA levels of individual UGT isoforms from clinical patients with liver diseases (Congiu et al, 2002) and mice with inflammation (Richardson et al, 2006) indicated downregulations of most UGT isoforms. The major limitation of previous studies concerning UGT regulation in liver injury is that the expression and enzyme activity of individual isoforms have not been concomitantly evaluated, resulting in inconsistencies across various studies with different measures.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest explanation is that the expression or activity of UGTs is decreased in NAFLD subjects. Nonalcoholic steatohepatitis, a specific subset of NAFLD, is characterized by hepatic steatosis and varying degrees of inflammation, which can lead to decreased UGT expression as has been observed in rodents (Richardson et al, 2006) and in human liver tissue (Congiu et al, 2002). Therefore, it is plausible that the major UGT isoforms involved in metabolism of silymarin may be lower in NAFLD subjects, resulting in higher plasma levels of parent flavonolignans and lower concentrations of conjugates.…”
Section: Cohortmentioning
confidence: 99%
“…The one demonstrated mechanism that is common in these conditions is, in part, oxidative stress (Kirby et al, 1994b;Chomarat et al, 1997;Nebert et al, 2000;Cheung et al, 2003;Gilmore et al, 2003;Gilmore and Kirby, 2004;Su and Ding, 2004;Weng et al, 2005;Chen and Siddiqui, 2007;Fisher et al, 2009;De-Oliveira et al, 2010). Furthermore, these conditions appear to be associated with increased serum bilirubin levels (Bonacini, 2004;Malaguarnera et al, 2005;Richardson et al, 2006b;Hansen, 2010). (Pellinen et al, 1993) Chloroform Anesthetic/Teflon (Camus et al, 1996) Cocaine Topical anesthetic (Pellinen et al, 1994a(Pellinen et al, , 1994b) Ethanol Fuel, beverage, and antiseptic (Lu et al, 2010) Phenobarbital Barbiturate and anticonvulsant (Hahnemann et al, 1992;SalonpÀÀ et al, 1994) Pyrazole Precursor for various medicines (Juvonen et al, 1985;Nichols and Kirby, 2008 (Cai et al, 2002) Buthionine sulfoximine Drug used in chemotherapy to reduce levels of glutathione (Gilmore et al, 2003) pregnenolone 16a-carbonitrile (PCN) Pregnane X receptor (PXR) agonist or antiglucocorticoid (Cai et al, 2002) Rifampicin Bactericidal antibiotics (Donato et al, 2000) Trans-4,5-dihydroxy-1,2-dithiane (DTTox) Intramolecular disulfide form of dithiothreitol; reducing agent (Gilmore and Kirby, 2004) (Montero et al, 1999) Bilirubin Bilirubin (BR) is the end product of heme catabolism, and heme is found in hemoglobin or other hemoproteins such as cytochromes, catalase, and a small pool of unbound free heme (Roy-Chowdhury et al, 2007).…”
Section: Pathophysiological States Associated With Cyp2a5mentioning
confidence: 99%